Utilization of banana puree fermented by Lactobacillus acidophilus LA5 and Bifidobacterium lactis BB12 for the manufacture of synbiotic ice cream - Abdullah Ismaeel Awad; Amer Hussein Hamdan Alzobaay (مجلة ديالى للعلوم الزراعية, 2023)
In this study, manufacturing synbiotic ice cream is containing fermented banana puree by Lactobacillus acidophilus LA5 and Bifidobacterium (Bif) lactis BB12 and probiotic ice cream containing fermented skim milk by the same bacteria under the same conditions. The Viability of probiotic starters, pH and sensorial properties were tested during the storage period, in addition to the overrun. Synbiotic ice cream showed high bacterial count for both species of probiotics, especially Ice.4 treatment (ice cream containing 10% fermented banana puree with same couple strains) which was 7.54 and 7.59 logarithmic (log) colony-forming unit (CFU)/ gram (g) for Lactobacillus (Lb). Acidophilus LA5 and Bif. lactis BB12, respectively, pH registered 5.7, sensorial attributes recorded 84% and overrun reached 78% compared to others trials that inoculated with 5% of the same puree or ice cream with fermented skim milk with (5,10) % or control treatment (without starters).